HESEB: The Helmholtz state-of-the-art Soft-X-Ray Undulator beamline at SESAME. Issue 1 (1st December 2022) - Abbadi, Anas; Attal, Maher; Bahrdt, Johannes; Drube, Wolfgang; Eberhardt, Wolfgang; Martin Esser, Frank; Follath, Rolf; Froideval, Annick; Fatih Genisel, Mustafa; Groetsch, Daniel; Rahman Hasoneh, Abdel; Huck, Maryam; et al.
Abstract: SESAME and a consortium of five Helmholtz Centers are designing and installing a state-of-the-art soft X-Ray undulator beamline at the SESAME light source in Amman, Jordan. Funding is provided by the Helmholtz Association over a four year project cycle that started in January 2019. This is an interim report covering the first 36 months of the project where the construction and installation has been almost completed and commissioning and characterization of the beamline is about to start. Additionally, seminars, workshops, and a training program are part of the project aimed at establishing a broad user community.